Reaching Older People With a Digital Fall Prevention Intervention in a Swedish Municipality Context—an Observational Study - Bajraktari, Saranda; Zingmark, Magnus; Pettersson, Beatrice; Rosendahl, Erik; Lundin-Olsson, Lillemor; Sandlund, Marlene (Frontiers in Public Health, 2022)
Background: There is robust evidence that falls in old age can be prevented by exercise programmes that include balance training, functional exercises, and strength training. For the interventions to have a population health impact, outreach to the target group with suitable interventions is needed. While digital interventions are promising there is limited knowledge on the characteristics of who is reached. The aim of this study was to describe the recruitment process, estimate reach rate at the population level and to describe participants characteristics and representativeness in a digital fall prevention intervention study. Methods: In a municipality-based observational study, reach of a digital fall prevention intervention was evaluated. The intervention included a digital exercise programme (Safe Step) and optional supportive strategies, complemented with a range of recruitment strategies to optimise reach. Recruitment during a period of six months was open to people 70 years or older who had experienced a fall or a decline in balance the past year. Reach was based on data from the baseline questionnaire including health and demographic characteristics of participants. Representativeness was estimated by comparing participants to a sample of older people from the Swedish National Public Health Survey. Results: The recruitment rate was 4.7% (n=173) in relation to the estimated target group (n=3706). The intervention attracted primarily women, older people with high education, individuals who used the internet or digital applications almost every day and those perceiving their balance as fair or poor. Safe step participants lived more commonly alone, had higher education and better walking ability in comparison to the Swedish National Public Health Survey. Conclusions: With a range of recruitment strategies most participants were recruited to a digital fall intervention during the first month. The intervention attracted primarily highly educated women who frequently used the internet or smart technologies. A higher diversity of intervention types is more likely to reach a larger group of older people with different needs.